2004
DOI: 10.1080/00365520410009609
|View full text |Cite
|
Sign up to set email alerts
|

Portal and systemic serum growth factor and acute-phase response after laparotomy or partial hepatectomy in patients with colorectal liver metastases: a prognostic role for C-reactive protein and hepatocyte growth factor

Abstract: PH is associated with a lower acute-phase and total IGF-I response and a higher HGF and IL-6 response compared with laparotomy. HGF and CRP responses had an influence on the prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 51 publications
2
16
0
Order By: Relevance
“…These authors concluded that the increases in VEGF and HGF reflect wound healing and systemic inflammation as a result of surgical trauma. Similar conclusions were obtained in a study in which growth factor levels were compared between patients that underwent a partial liver resection and patients that underwent a laparotomy but did not undergo a partial hepatectomy as the tumor was found unresectable during surgery and in a study on VEGF levels following major abdominal surgery [35,36].…”
Section: Discussionsupporting
confidence: 71%
“…These authors concluded that the increases in VEGF and HGF reflect wound healing and systemic inflammation as a result of surgical trauma. Similar conclusions were obtained in a study in which growth factor levels were compared between patients that underwent a partial liver resection and patients that underwent a laparotomy but did not undergo a partial hepatectomy as the tumor was found unresectable during surgery and in a study on VEGF levels following major abdominal surgery [35,36].…”
Section: Discussionsupporting
confidence: 71%
“…Of these, the value of C-reactive protein is most recognized being associated with cancer cachexia 21,22 ), compromised cell-mediated immunity, 23,24 and upregulation of growth factors and angiogenesis. 25,26 Nevertheless, the mechanisms underlying the relationship between local and systemic inflammatory responses and cancer-specific survival are likely to be complex. These include extrinsic pathways such as nutritional and functional decline, immune dysfunction and tumor angiogenesis, growth, and dissemination.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, 33 studies were assessed by screening the full-text, among which 24 articles were excluded. Eventually, nine studies were included in the meta-analysis [5, 1017]. …”
Section: Resultsmentioning
confidence: 99%
“…Most of the studies were conducted in developed countries, such as the USA, Germany, Netherlands, Japan and Turkey. Data on patients in six studies were collected from 1991 to 2014, while other studies did not mention the collection time [5, 13, 17]. Altogether, the nine studies included 777 patients, and each study contained samples that ranged from 18 to 184 patients.…”
Section: Resultsmentioning
confidence: 99%